2012
DOI: 10.1258/ijsa.2012.011342
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis is conducive to the persistence of HPV infection

et al.

Abstract: We investigated the effects of bacterial vaginosis (BV) on the outcomes of high-risk human papillomavirus infection (HR-HPV). BV was diagnosed on Papanicolaou-stained cytology slides of 707 HPV-positive patients. HR-HPV DNA expression was analysed using the Hybrid Capture II (HC-II) assay. Of the 707 HR-HPV-positive female patients, 298 (42.1%) exhibited clearance of HR-HPV. The remaining 409 patients had persistent HR-HPV infection. The persistent HR-HPV group and the clearing group had similar rates of BV at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 26 publications
4
61
0
1
Order By: Relevance
“…There is also evidence to suggest that persistence is more likely in those with altered microbiome. In one study, women with persistent high risk (hr) HPV had a prevalence of BV of 11% compared to only 5% in those women who cleared their hrHPV 75 . Similarly, King et al 76 found that women diagnosed with BV had delayed clearance of HPV (adjusted Hazard ratio (aHR)=0.84, 95%CI: 0.72, 0.97).…”
Section: Hpv Infection and The Vaginal Microbiomementioning
confidence: 99%
“…There is also evidence to suggest that persistence is more likely in those with altered microbiome. In one study, women with persistent high risk (hr) HPV had a prevalence of BV of 11% compared to only 5% in those women who cleared their hrHPV 75 . Similarly, King et al 76 found that women diagnosed with BV had delayed clearance of HPV (adjusted Hazard ratio (aHR)=0.84, 95%CI: 0.72, 0.97).…”
Section: Hpv Infection and The Vaginal Microbiomementioning
confidence: 99%
“…The Hay/Ison criteria used for diagnosis of BV in the UK is largely based on the presence or absence of both Lactobacillus and Gardnerella or Mobiluncus morphotypes [27]. BV has previously been correlated with higher incidence, prevalence and persistence of HPV infection and with development of CIN [2831]. However, other studies did not find a positive correlation between CIN and BV [32–34], which may partly be explained by the lack of objective diagnostic tests for BV, the reliance on subjective scoring systems [35] and the heterogeneity of BV itself.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginosis was observed in 9.1% of patients who were HC2-negative for HPV, while vaginosis was observed in 22.4% of HC2-positive patients (p=0.012). Guo et al (25) reported that, compared to women without BV, women with BV had a lower clearance of HPV infection. All these findings can be explained by the hypothesis that susceptibility to HPV and the immune system's ability to clear HPV can be affected by vaginal bacterial infections, which disrupt the balance of the vaginal microbiota (7,26) .…”
Section: Discussionmentioning
confidence: 99%